Inhibition of activin A signalling in a mouse model of pre-eclampsia. Issue 8 (August 2015) - Lim, R.; Adhikari, S.; Gurusinghe, S.; Leaw, B.; Acharya, R.; Rahman, R.; Ciayadi, R.; Potdar, M.; Kelso, G.F.; Hearn, M.T.W.; Wallace, E.M.
Abstract Introduction Pre-eclampsia remains a major cause of maternal and fetal morbidity and mortality. Despite intensive research over the last 50 years, significant therapeutic advances have yet to be realised. We recently reported on the role of activin A in the pathophysiology of pre-eclampsia, whereby a pre-eclampsia-like disease state was induced in pregnant mice through activin A infusion. Using the same animal model, the effects of inhibiting activin A signalling on this pre-eclampsia-like disease state have now been assessed with low molecular weight compounds structurally related to activin-receptor-like kinase (ALK) inhibitors. Methods 23 synthetic compounds were screened for ability to reduce activin A-induced free radical production in HUVECs. Further, following administration of activin A (50 μg) via a subcutaneous mini-osmotic pump from day 10 of pregnancy, the most active inhibitor, MKP-1-140A, (1 mg/kg) was also concomitantly administered via subcutaneous injections. Results Significant reductions in activin A-induced systolic blood pressure and urine albumin:creatinine ratio were observed with inhibitor-treated animals. However, these findings were accompanied by sustained elevation of liver enzymes and albumin extravasation in the brains of pregnant mice that received MKP-1-140A. Furthermore, inhibition of activin A signalling with MKP-1-140A failed to rescue fetal growth restriction, and treatment with MKP-1-140A alone resulted in craniofacial and karyotypic abnormalities. Discussion These data indicate that whilst inhibition of activin A signalling by the low molecular weight ALK kinase inhibitor, MKP-1-140A, reduced some of the physiological manifestations of pre-eclampsia, the potential for serious maternal and fetal side effects may preclude it from clinical applications.